2012
DOI: 10.1158/1078-0432.ccr-11-2599
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Prognosis and Biology of Breast Cancer Arising in Young Women Using Gene Expression Profiling

Abstract: Purpose: Breast cancer in young women is associated with poor prognosis. We aimed to define the role of gene expression signatures in predicting prognosis in young women and to understand biological differences according to age.Experimental Design: Patients were assigned to molecular subtypes [estrogen receptor (ER)À )] using a three-gene classifier. We evaluated whether previously published proliferation, stroma, and immune-related gene signatures added prognostic information to Adjuvant! online and tested th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
258
3
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(287 citation statements)
references
References 48 publications
17
258
3
9
Order By: Relevance
“…Luminal A cancer, with better prognosis, was detected in 35% of the older and 17% of the younger women [17]. However, it seems that worse tumor biology in patients with BC is not only connected with less beneficial distribution of particular molecular subtypes of cancer.…”
Section: Tumor Biologymentioning
confidence: 99%
“…Luminal A cancer, with better prognosis, was detected in 35% of the older and 17% of the younger women [17]. However, it seems that worse tumor biology in patients with BC is not only connected with less beneficial distribution of particular molecular subtypes of cancer.…”
Section: Tumor Biologymentioning
confidence: 99%
“…5 However, molecular studies have also suggested that breast cancer in young patients may be characterized by unique disease biology, as compared to older patients, beyond subtype distribution. 6 One of the predisposing factors for breast cancer is germline mutation in tumor suppressor genes such as BRCA1/2. In younger patients its frequency may be as high as 10.9 to 23%, as reported in women from different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer arising in young women exhibits distinct biological features and has been shown to pursue an aggressive clinical behavior (Cancello et al 2010, Azim et al 2012a, Collins et al 2012, Narod 2012. Among the unique situations that young women with breast cancer may face is pregnancy.…”
Section: Introductionmentioning
confidence: 99%